Perception de la néographie phonétisante dans le DEM : retour sur la néographie qu / k - Lazar, Jan (Neophilologica, 2015)
The specific context of the realization of electronic discourse joins together two distinct enunciation modes: written and oral. The former one is restrained by the conditions of the realization of electronic discourse, the messages are merely written. The latter one poses many problems on orthographic level. The hybridization of these two modes, written and oral, tends to create new orthographical rules that would correspond to the economy of expression. In the present study, the author would like to compare the frequency of neography que / k in different types of computer mediated communication.